Suitability of personnel for work in the intelligence and security services - Alispahić, Bakir (Technium Social Sciences Journal, 2021)
Intelligence and security services as specific, specialized and highly professional services, in modern times, are made up of people - rational (sometimes irrational) and intelligent beings. Consequently, it is necessary to take all activities and measures so that the best of the best enter the ranks of such important state institution that deals with the security of both the state and the nation. Selection and education of people with certain abilities is crucial for the functioning of the service as a specific, specialized and highly professional service. Personnel, as the basis of work, require much more attention than is given to them in certain services, and it is necessary to understand the problem of inadequate personnel - both those who are unable to do their job and those who are prepared to secretly perform work for themselves, some other foreign, or enemy service. The evolution of conventional war into the modern, Special War, has found a means of destructiveness in the intelligence and security services, which are fighting in an unconventional way in a world where conventional, armed war no longer makes sense. Special attention must be paid to the problem of personnel in the intelligence and security services in order to find and apply adequate solutions for the protection of their personnel from hostile influences, thus protecting the state, nation and society.